El "saber artístico" de un antropólogo y el estudio de la cultura en el Perú. A propósito de una obra olvidada de José María Arguedas - Rivera Andía, Juan Javier (2011)
This text aims to make some questions about the reasons why an ethnographic archive joined by Jose Maria Arguedas has remained unpublished until now. Mainly, it is suggested that this lack of attention to a source like this may be related to a the way in which Arguedas conceived the production of knowledge in Anthropology.